2017
DOI: 10.3390/geosciences7040120
|View full text |Cite
|
Sign up to set email alerts
|

The Need for Geoethics Awareness from a Canadian Perspective

Abstract: An online survey of Canadian Earth scientists on geoethics-defined as the interconnection between humanity and Earth sciences-asked participants to (1) rate the importance of issues around scientific integrity, social responsibility, aboriginal concerns, corporate ethics, and fieldwork; (2) identify ethical considerations they had observed; and (3) tell us how they were introduced to ethical viewpoints and whether their undergraduate programs had prepared them for ethical decision-making. Despite a small sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
(6 reference statements)
0
3
0
Order By: Relevance
“…In my readings of the geoethics literature, however, I have not found perspectives that adequately address the moral and ethical complexities of producing minerals as commodities for trade, where wealth and corporate profits may be generated by violent conflicts, or where end material uses may be demonstrably unsustainable. Integration of geoethical training into undergraduate education has been identified as a key opportunity to improve sociocultural and ethical decision-making for geoscientists (Mogk et al, 2018;Mogk & Bruckner, 2020;Ryan & Bank, 2017), and teaching modules are available from the National Association of Geoscience Teachers website Teach the Earth (Mogk, n.d.) and GeoContext (Pico et al, n.d.). But despite broad recognition of the local, regional and global implications of geoscientific research and professional practice, with some suggesting that geoscientists have a responsibility to act as "spokespeople for an unstable Earth" (Castree, 2017, p. 54; see also Bjornerud, 2018), geoscientists continue to be socialized and educated to avoid value judgements in their work (Castree, 2017).…”
Section: Figurementioning
confidence: 99%
“…In my readings of the geoethics literature, however, I have not found perspectives that adequately address the moral and ethical complexities of producing minerals as commodities for trade, where wealth and corporate profits may be generated by violent conflicts, or where end material uses may be demonstrably unsustainable. Integration of geoethical training into undergraduate education has been identified as a key opportunity to improve sociocultural and ethical decision-making for geoscientists (Mogk et al, 2018;Mogk & Bruckner, 2020;Ryan & Bank, 2017), and teaching modules are available from the National Association of Geoscience Teachers website Teach the Earth (Mogk, n.d.) and GeoContext (Pico et al, n.d.). But despite broad recognition of the local, regional and global implications of geoscientific research and professional practice, with some suggesting that geoscientists have a responsibility to act as "spokespeople for an unstable Earth" (Castree, 2017, p. 54; see also Bjornerud, 2018), geoscientists continue to be socialized and educated to avoid value judgements in their work (Castree, 2017).…”
Section: Figurementioning
confidence: 99%
“…For example, an email (J. Gierke, chairman of the Department of Geological and Mining Engineering and Sciences, Michigan Tech personal communication, 3 February 2016) states "In terms of social responsibility there is one undergraduate course where social responsibility is pervasive: Environmental Geology" (see also Gosselin et al, 2016). Geoethics (Peppoloni and Di Capua, 2015), the concept that explores the overlap between geosciences and ethics, has important social responsibility implications, and this subject has been proposed to be introduced into the undergraduate programs in Canada and elsewhere (Ryan and Bank, 2017). Three universities in the USA have commenced CSR course modules for their mining and petroleum-engineering students that may be relevant to other areas of geoscience education as well (Smith and Lucena, 2018).…”
Section: Social Responsibility In Geosciences Study Programsmentioning
confidence: 99%
“…Reis and Galvao (2009) argue that most students wrongly perceive science as a linear process and that including socio-scientific issues as an integral part of the curriculum can promote ethical awareness and scientific literacy. Ryan and Bank (2017) surveyed Canadian geoscientists and found that most respondents did not think that their programs had prepared them for ethical decision making.…”
Section: Introductionmentioning
confidence: 99%